Вычислите,используя формулы сокращенного умножения: а) [latex]\frac {39^{3} + 41^{3}}{80 } -( 39^{2} + 41^{2} )[/latex] б)[latex]\frac{48^{3}-52^{3}}{-4} -(48^{2}+52^{2})[/latex]
Вычислите,используя формулы сокращенного умножения:
а) [latex]\frac {39^{3} + 41^{3}}{80 } -( 39^{2} + 41^{2} )[/latex]
б)[latex]\frac{48^{3}-52^{3}}{-4} -(48^{2}+52^{2})[/latex]
Ответ(ы) на вопрос:
Гость
a) [latex]\frac{39^{3}+ 41^3}{80}-(39^2 + 41^2) = \frac{(39+41)(39^2 - 39*41 + 41^2)}{80} -(39^2 + 41^2) =[/latex]
[latex]= 39^2 - 39*41 + 41^2 - 39^2 - 41^2 = -39*41 = -1599[/latex]
б) [latex]\frac{48^3 - 52^3}{-4} - (48^2 + 52^2) = \frac{(48-52)(48^2 + 48*52 + 52^2)}{-4} - (48^2 + 52^2) =[/latex]
[latex]= 48^2 + 48*52 + 52^2 - 48^2 - 52^2 =2496[/latex]
Не нашли ответ?
Похожие вопросы